2021
DOI: 10.3390/antiox10111748
|View full text |Cite
|
Sign up to set email alerts
|

Whey- and Soy Protein Isolates Added to a Carrot-Tomato Juice Alter Carotenoid Bioavailability in Healthy Adults

Abstract: Recent findings suggested that proteins can differentially affect carotenoid bioaccessibility during gastro-intestinal digestion. In this crossover, randomized human trial, we aimed to confirm that proteins, specifically whey- and soy-protein isolates (WPI/SPI) impact postprandial carotenoid bioavailability. Healthy adults (n = 12 males, n = 12 females) were recruited. After 2-week washout periods, 350 g of a tomato-carrot juice mixture was served in the absence/presence of WPI or SPI (50% of the recommended d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 53 publications
1
12
0
Order By: Relevance
“…Similarly, significant differences on the postprandial plasma AUC of TRL-carotenoid concentrations (nmol h L −1 ) between WPI and SPI for individual carotenoids, that is, phytoene (160 ± 3.3 versus 82 ± 3.3), phytofluene (55 ± 0.9 versus 31 ± 0.9), and 𝛼-carotene (14 ± 0.6 versus 3 ± 0.6) were observed. [14] This was the first study reporting an effect of added proteins on carotenoid absorption in humans, confirming the previously reported in vitro results, pointing out that a well digestible protein such as WPI could be beneficial for carotenoid bioavailability, whereas the less digestible SPI resulted in hampered bioavailability of carotenoids. The lower digestibility of SPI versus WPI has been earlier emphasized, for instance in studies focusing on sport supplements, with SPI showing significantly slower breakdown into amino acids.…”
Section: Studies Based On In Vivo Trialssupporting
confidence: 88%
See 4 more Smart Citations
“…Similarly, significant differences on the postprandial plasma AUC of TRL-carotenoid concentrations (nmol h L −1 ) between WPI and SPI for individual carotenoids, that is, phytoene (160 ± 3.3 versus 82 ± 3.3), phytofluene (55 ± 0.9 versus 31 ± 0.9), and 𝛼-carotene (14 ± 0.6 versus 3 ± 0.6) were observed. [14] This was the first study reporting an effect of added proteins on carotenoid absorption in humans, confirming the previously reported in vitro results, pointing out that a well digestible protein such as WPI could be beneficial for carotenoid bioavailability, whereas the less digestible SPI resulted in hampered bioavailability of carotenoids. The lower digestibility of SPI versus WPI has been earlier emphasized, for instance in studies focusing on sport supplements, with SPI showing significantly slower breakdown into amino acids.…”
Section: Studies Based On In Vivo Trialssupporting
confidence: 88%
“…[12] It has recently been shown that well digested proteins, such as those present in whey protein isolate (WPI), are able to modify the bioavailability of liposoluble microconstituents, such as carotenoids from a juice, both in vitro [13] and in vivo. [14] Similarly, for vitamin D3, a positive effect on postprandial absorption in mice was found following the simultaneous intake of WPI. [15] The positive effects of proteins on the absorption of liposoluble microconstituents are thought to be related to the following features: (a) Emulsifying properties, that is, produced peptides during digestion could foster the solubility and stability of lipid droplets while interacting with their surface, promoting their processing into mixed micelles [16] ;…”
Section: Introductionmentioning
confidence: 94%
See 3 more Smart Citations